Evaluation of the Performance of Mekong Lestari Village-Owned Enterprise: Contribution in Improving the Economy in Mekong Village - Hardian Setiadi; Ahmad Fitra Yuza; Khairul Rahman; Dita Fisdian Adni (International Conference On Law And Social Sciences, 2024)
Village-owned enterprises, referred to as BUMDes, are economic institutions owned by the village to manage economic activities at the village level. The main objective of establishing BUMDes is to improve the village economy, create jobs, and improve the welfare of the village community. By evaluating the performance of BUMDes Mekong Lestari, the success of BUMDes Mekong Lestari in improving the economy and welfare of the community in Mekong Village will be known. This research aims to evaluate the performance of BUMDes Mekong Lestari, Mekong Village, Tebing Tinggi Barat Sub-district, Meranti Islands Regency, Riau Province. Qualitative research methods are used in this study with data collection techniques, namely interviews, observation, and documentation. From this research, it can be concluded that the performance of BUMDes Mekong Lestari has not been maximized. The performance of BUMDes that has not been maximized cannot be separated from the many obstacles and constraints faced in managing BUMDes Mekong Lestari, such as the lack of human resources who are reliable in their fields, lack of facilities and infrastructure and lack of understanding and awareness of the village community of the existence of BUMDes